If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2(4 + 9a) = 0 2 + (4 * -2 + 9a * -2) = 0 2 + (-8 + -18a) = 0 Combine like terms: 2 + -8 = -6 -6 + -18a = 0 Solving -6 + -18a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -18a = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -18a = 0 + 6 -18a = 0 + 6 Combine like terms: 0 + 6 = 6 -18a = 6 Divide each side by '-18'. a = -0.3333333333 Simplifying a = -0.3333333333
| -6+9(x-1)=16x+2-7x | | 9+2i=0 | | 7(x+4)-3=29-2x-4+9x | | -28=x-3.7 | | 200/x=3x | | 1/4-x=3/x | | (d^3+d^2-4d)y=0 | | 4(b+3)=9 | | 12x+11=156 | | 28y+4x=4 | | -3p/2;0 | | x^2=16y-32 | | 25=18-2y | | -2(5x-9)+7=-10X+25 | | -26=9+5x | | 7x(2)=63 | | (3/5)2 | | 0.25x=(9/365)x | | x^4-12x^3+36x^2-20x+3=0 | | x+(x*.12)=765 | | I-(1+7x)-6(-7-x)=36 | | 15/20=3/x | | 8.3w-w-8.9=1.5 | | -6x-6=10 | | 19/21-2/3 | | 6y+9=2thirdsx | | -6x+3=10 | | X^2-45x+506=0 | | (-2/7)^3 | | [9(n+5)-19]-[3(n-4)+2]= | | -6x-3=10 | | -100a^2-9=0 |